Combined hot air convective drying and microwave-vacuum drying of blueberries (Vaccinium corymbosum L.): Drying kinetics and quality characteristics. Issue 6 (25th April 2016) - Zielinska, Magdalena; Sadowski, Piotr; Błaszczak, Wioletta
ABSTRACT: The aims of this study were to: (1) evaluate the effect of each stage of HACD + MWVD on the drying kinetics and quality parameters of blueberries, including color, overall appearance, mechanical and physical attributes, and rehydration potential; (2) select proper combination order and conversion point of HACD + MWVD to minimize physicochemical changes and maintain high quality of blueberries. The results were compared with HACD and MWVD alone. A linear equation produced a good fit to data describing the drying kinetics of the constant or first falling rate period, whereas the Henderson and Pabis model was a good fit for the dataset describing the second falling rate period. The color changes induced in berries by HACD + MWVD were limited ( ΔE* ranged from 3.08 ± 2.25 to 3.65 ± 2.28) in comparison with HACD ( ΔE* ranged from 7.90 ± 2.29 to 8.21 ± 1.77). HACD + MWVD contributed to the achievement of significantly lower values of hardness, chewiness, and gumminess in blueberries, compared to HACD. Multi-stage HACD + MWVD with hot air predrying at 80°C until the achievement of the moisture content of 1.95 ± 0.05 kg · kg −1 db caused the lowest shrinkage of blueberries. Blueberries dried by multi-stage HACD +MWVD with hot air predrying at 80°C until the achievement of moisture content of 1.95 ± 0.05 kg · kg −1 db were characterized by the highest rehydration potential, in terms of moisture content, rehydration ratio, and water gain; i.e., 4.15 ± 0.02 kg · kg −1 db, 4.02 ± 0.05 g · g −1 db, 4.07 ± 0.01 g · g −1 db, respectively.